Lightning Protection Of Pole-Mounted Transformers And Its Applications - Chan, Chee Pin (Universiti Sains Malaysia, 2006)
Lightning is the single most important cause of failure in medium voltage distribution system. Analysis carried out by world wide utilities has shown that the failure rate of the pole-mounted transformer caused by lightning in medium voltage system goes as high as 4.5-5.0%. This is mainly due to improper installation of lightning arrester and also there is no well established method to access the performance of lightning protection. The objectives of this study are to provide a general bench mark for lightning protection of pole-mounted transformer in medium voltage system and to ensure proper installation of surge arrester to reduce the failure rate of the transformer. Research has found out that the high failure rate of pole-mounted transformer is due to the excessive separation length between the surge arrester and the terminal of the transformer. A method has been proposed that the separation length is determined so that the failure rate of the transformer is below a certain value. With this method, a case study on the lightning protection of pole-mounted transformer of 11kV distribution system in Malaysia is carried out. A program prototype based on this method is also developed with Matlab to deal with the tedious hand calculations of integration and probability. This program is applied to the case study above to further verify the results of hand calculation. In this case study, with parameters of ground flash density (Ng) = 5.8 flashes per m2 per year, horizontal span of two outmost conductors (b) = 1.07m, conductor height (H) = 7.525m, shielding factor (Sf) = 0.4, transformer lifetime (LF) = 20 years, failure rate (FR) = 5%, maximum surge current (I0) = 300kA, safety margin (sm) = 20%, residual voltage of arrester (Up) = 32kV, basic insulation level (BIL) = 75kV, wave front time (tf) = 5µs, line surge impedance (Z0) = 450Ω, and arrester length (lmin) = 1m, the optimum separation length calculated by the program is 1.3219m. This means that in order to achieve a failure rate of 5% throughout the lifetime of the transformer, surge arrester should be installed 1.3219m from the transformer terminal.